Analysis of Similiarities and Differences Between Bugis and Han Ethnicities in Marriage Tradition - Nirdayanti M; Sri Khaerani Rahman (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2023)
Indonesia and China are countries that are now increasingly opening up opportunities for cooperation in various sectors. This has made many people and entrepreneurs take advantage of this opportunity to get involved in it. This can be seen from the surge of immigrants from China to Indonesia, Indonesia to China, bringing their own provisions and goals. However, because different countries and different cultures can trigger cultural conflicts, as a result, this creates a need for both countries to have cultures with each other. Therefore this article focuses on culture, it shows the culture of marriage from one of the ethnicities of the two countries, the Bugis and Han ethnicities. In addition, this research allows people to gain insight into differences and similarities in ethics, traditions and cultural values and kinship between cultures. Applying comparative methods, literature surveys and secondary data analysis to show the similarities and differences in the marriage culture of the Bugis and the Han people, by reviewing the marriage traditions and the meaning of marriage of the two ethnicities. This research reveals that traditional culture plays a major role in every marriage culture, history, to religion.